English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

^3 square root of 6x = -3

2007-03-13 02:29:18 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

4 answers

solve for x
6x = -3
6/6 x = -3/6
x = -1/2
square root of -.5 = .707

2007-03-13 02:36:02 · answer #1 · answered by Curly 4 · 0 0

I assume you mean the cube root of 6 = -3 this can be written as:

(6x)^1/3 = -3

cube both sides:

6x = -27
x = -27/6 =9/2

2007-03-13 03:33:35 · answer #2 · answered by bignose68 4 · 0 0

sqrt(5x + 29) = x+ 3 sq. the two components 5x + 29 = x^2 + 6x + 9 Now isolate the equation to a minimum of one area and set it to 0. 0 = x^2 + x - 20 Now element and clean up for x. 0 = (x+5)(x-4) x = -5 or 4

2016-12-14 17:52:53 · answer #3 · answered by hannigan 4 · 0 0

What do you mean with [ ^3 ] ?????

Can I understand that are you asking

(6X)^(1/3) = -3 (the cubic root of 6X = -3)?

If I'm correct:

(6X)^(1/3) = -3 ==> [(6X)^(1/3)]^3 = [-3]^3
6X = -27
X = -27/6
X = -9/2

2007-03-17 00:26:47 · answer #4 · answered by Apolo 6 · 0 0

fedest.com, questions and answers